Information technologies in teaching humanitarian disciplines - Morozova, Irina M. (2020)
The use of information technology in teaching humanitarian disciplines contributes to the formation of highly qualified, competitive specialists who can adapt to rapidly changing conditions, possessing a high level of development of critical and creative thinking, ready for professional self-development and self-improvement, for the implementation of reflection, capable of setting goals and systematically achieving them. The work actualizes the importance of information technology in the training of highly qualified competitive specialists capable of implementing professional activities at a high level. The purpose of the article is to analyze the experience of implementing information technologies in teaching humanitarian disciplines. Smart boards, multimedia installations, document cameras, electronic textbooks, electronic educational platforms and others were used as information technologies used in the teaching of the humanities. The study made it possible to reveal the influence of information technologies on the level of formation of students' competencies.